2017
DOI: 10.1039/c7cc00273d
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic asymmetric Meerwein–Ponndorf–Verley reduction of glyoxylates induced by a chiral N,N′-dioxide/Y(OTf)3complex

Abstract: An asymmetric Meerwein-Ponndorf-Verley (MPV) reduction of glyoxylates was for the first time accomplished via an N,N'-dioxide/Y(OTf) complex with aluminium alkoxide and molecular sieves (MSs) as crucial additives. A variety of optically active α-hydroxyesters were obtained with excellent results. A possible reaction mechanism was proposed based on the experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…After washing with brine solution, the combined organic extracts were dried over Na 2 SO 4 and concentrated by rotary evaporation. The residue was purified by flash chromatography (petroleum ether/ethyl acetate = 10:1) to afford the protected intermediate as a clear oily liquid (2.108g, 78%) yield …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After washing with brine solution, the combined organic extracts were dried over Na 2 SO 4 and concentrated by rotary evaporation. The residue was purified by flash chromatography (petroleum ether/ethyl acetate = 10:1) to afford the protected intermediate as a clear oily liquid (2.108g, 78%) yield …”
Section: Methodsmentioning
confidence: 99%
“…The residue was purified by flash chromatography (petroleum ether/ethyl acetate = 10:1) to afford the protected intermediate as a clear oily liquid (2.108g, 78%) yield. 24 The next step was followed by the general procedure for the synthesis of 1 (3 mmol scale). Isolated yield: orange oil; 596.0 mg, 67% yield.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Generally, the MPV reduction mechanism involves intermolecular hydride transfer from sacrificial alcohols to carbonyl compounds via a six-membered ring transition state . Owing to its carbonyl-specific chemoselectivity and environmentally friendly process, intensive efforts to develop various catalytic systems of MPV reduction have been made, such as inorganic bases, boron alkoxides, and transition-metal systems. , So far, scandium is rarely used as a metal catalyst for the MPV reaction . Sc­(OTf) 3 is an environmentally friendly Lewis acid and had shown widespread application in organic transformation .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these prominent advances of the MPV reaction, the principal challenges for further improving such reduction are still noticeable. Designing a new method for the MPV reduction by any primary and secondary alcohols that can be used as a hydride source, rather than using a secondary alcohol such as 2-propanol, is highly desirable. …”
Section: Introductionmentioning
confidence: 99%
“…Wu et al introduced a chiral N , N ‐dioxide/Y(OTf) 3 complex to bring about the reduction of glycosylates. It was found that the adjunction of both molecular sieves and Al(OtBu) 3 was effective for the reaction . There are many catalysts used in the CTH reaction, but for this kind of reaction there still exist limiting factors, such as a high reaction temperature, a long reaction time, complex operation of the catalyst preparation process, and expensive catalyst materials.…”
Section: Introductionmentioning
confidence: 99%